Socially Acceptable CO2 Prices - Sebastian Dullien; Ulrike Stein (Wirtschaftsdienst)
Abstract This article considers the conditions under which a carbon tax or other CO2 emissions pricing mechanisms can be seen as “socially balanced” and the appropriate economic policy instruments to achieve this goal. A broad set of instruments should be used that not only address relative price changes in the consumption basket but also potential job losses in the transition towards a carbon-neutral economy.